Global Pollution of Surface Waters from Point and Nonpoint Sources of Nitrogen - G. van Drecht; A.F. Bouwman; J.M. Knoop; C. Meinardi; A. Beusen (The Scientific World Journal)
Global 0.5- by 0.5-degree resolution estimates are presented on the fate of nitrogen (N) stemming from point and nonpoint sources, including plant uptake, denitrification, leaching from the rooting zone, rapid flow through shallow groundwater, and slow flow through deep groundwater to riverine systems. Historical N inputs are used to describe the N flows in groundwater. For nonpoint N sources (agricultural and natural ecosystems), calculations are based on local hydrology, climate, geology, soils, climate and land use combined with data for 1995 on crop production, N inputs from N fertilizers and animal manure, and estimates for ammonia emissions, biological N fixation, and N deposition. For point sources, our estimates are based on population densities and human N emissions, sanitation, and treatment. The results provide a first insight into the magnitude of the N losses from soil-plant systems and point sources in various parts of the world, and the fate of N during transport in atmosphere, groundwater, and surface water. The contribution to the river N load by anthropogenic N pollution is dominant in many river basins in Europe, Asia, and North Africa. Our model results explain much of the variation in measured N export from different world river basins.